Maintaining the Existence of the Mosque, Preserving Islamic History: Lessons from Masjid Jamik Siulak Mukai, Kerinci - Della, Ansri; Fernando, Pito (Contemporary Society and Politics Journal, 2023)
The existence of mosques serves as one of the proofs of the Islamization process in Indonesia, as well as historical evidence of the development of Islam. This research aims to trace the role and significance of mosques in the Islamization process. Masjid Jamik Siulak was chosen as the research object due to its authentic historical background in spreading Islam among the Kerinci community in Jambi. This study is a qualitative research that employs three data collection techniques: observation, interviews, and documentation. The results of this research indicate that Masjid Jamik Siulak, besides being a place of worship, also plays a role in social activities and the education of teenagers and children. These roles have been in place since the early development of Islam until the present, making Masjid Jamik Siulak an important evidence in the development of Islam in Kerinci.